A Mathematical Model of the Mud Crab (Scylla Sp.) Involving Cannibalism and Refuge - Abubakar, Agung Sucipto; Panigoro, Hasan S.; Djakaria, Ismail; Nuha, Agusyarif Rezka; Hasan, Isran K.; Asriadi, Asriadi (Gammarise Publishing, 2025)
Cannibalism, a common ecological phenomenon in various species, significantly impacts the population dynamics of mud crabs (Scylla sp.). This study develops a mathematical model to analyze the effects of cannibalism and protective refuges on the population sustainability of juvenile and adult mud crabs. The model identifies two equilibrium points: the extinction equilibrium and the coexistence equilibrium. Stability analysis using the Jacobian matrix reveals that the extinction equilibrium is locally asymptotically stable under specific conditions. In contrast, the coexistence equilibrium depends on the transition rate from juvenile to adult crabs and the effectiveness of protective measures. Numerical simulations demonstrate that increasing the transition rate and implementing higher levels of refuge protection mitigate the adverse effects of cannibalism, enhancing population stability. These findings provide a quantitative foundation for sustainable fisheries management and conservation strategies for mud crab populations in mangrove ecosystems.